Preparation and in vitro release of zein microparticles loaded with prednisolone for oral delivery - Lau, E.; Johnson, Stuart; Mikkelsen, D.; Halley, P.; Steadman, K. (Informa Healthcare, 2012)
Zein has been proposed as a polymer for targeted-drug delivery via the oral route. Zein microparticles were loaded with prednisolone and evaluated as an oral delivery system. Microparticles were formulated using phase separation. Starting quantities of zein and prednisolone, along with the agitation method and temperature were found to significantly impact drug loading and loading efficiency. Vortex mixing produced the highest drug loading and loading efficiency. Drug release was measured in simulated conditions of the stomach and small intestine using the microparticles made with the method that best improved drug loading. In simulated stomach and small intestine conditions, prednisolone release reached almost 70% over 3 and 4 h, respectively. While a clinically relevant dose may be delivered using c. 100 mg of zein microparticles, prednisolone release from the microparticles indicates that they may not be suited as a controlled- or targeted-delivery system.